Sectoral Interdependence and Business Cycle Synchronization in Small Open Economies - Drago Bergholt; Tommy Sveen (Norges Bank, 2014)
Existing DSGE models are not able to reproduce the observed influence of international business cycles on small open economies. We construct a two-sector New Keynesian model to address this puzzle. The set-up takes into account intermediate trade and producer heterogeneity, where goods and service industries differ in terms of i) price flexibility, ii) trade intensity, iii) technology, iv) I-O structure, and v) the volatility of productivity innovations. The combination of intermediate markets and heterogeneous producers makes international business cycles highly important for the small economy, even if it has a large service sector. Exploiting I-O matrices of Canadian and US industries, the model is able to reproduce the role of international disturbances typically found in empirical studies. Model simulations deliver cross-country correlations in macroeconomic variables of about 0:7, with half of the variation in domestic variables attributed to foreign shocks.
hdl:11250/2495981
Keywords: E32; F41; F44; 330; small open economy; multi-sector; intermediate trade; international business cycles